ANALISIS PENGUKURAN POSTUR KERJA PADA AKTIVITAS MANUAL MATERIAL HANDLING DI PT JMS BATAM - Sidabutar, Fashion Dedy; Zetli, Sri (LPPM Universitas Putera Batam, 2023)
This study aims to analyze the risk level of Musculoskeletal Disorders (MSDs) in workers who carry out Manual Material Handling (MMH) activities at PT JMS Batam. MMH is a manual transportation and material transfer activity using human labor. This study was conducted because MMH activities carried out repetitively often cause health complaints, especially in the skeletal muscles. The primary data collection method is carried out through observation, direct interviews with employees, documentation using mobile phone cameras, and the distribution of Nordic Body Map (NBM) questionnaires to identify complaints on workers' body parts. The Rapid Entire Body Assessment (REBA) method is used to assess the posture of workers during MMH activities. The results showed that Nordic Body Map analysis showed that all stevedoring workers had the potential to experience musculoskeletal disorder complaints, especially on the left shoulder, right shoulder, back, waist, and buttocks. Workers with scores above 70 are at high risk and need immediate improvement. Workers scoring 55-70 are at moderate risk and require consideration of future improvements. Analysis using the REBA method showed that material transfer has a high risk of trunk and upper arm posture, increasing the risk of injury and health problems.